The enhancement of optical processes near rough surface of metals - Dovbeshko, G.I.; Fesenko, O.M.; Shirshov, Yu.M.; Chegel, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Last decades the enhancement of optical transitions near metal surface was observed under study the optical processes (luminescence, Raman scattering, IR absorption). The effect consists in an essential increase of the intensity of transition (for example, an effective cross-section increases by factor 10⁵…10¹¹ for Raman scattering and 10…10⁴ for IR absorption) or efficiency of the processes near metal surface (e.g. generation of second harmonic). We have analyzed a various experimental techniques that made it possible to achieve an enhancement in surface enhanced infrared absorption (SEIRA), surface enhanced Raman scattering (SERS), metal-enhanced fluorescence. Under the conditions of our experiment and according to literature data, there was observed enhancement factor which equal to 3…20 for vibrations of various molecular groups in SEIRA. Peculiarity of another optical amplifier, namely, colloidal gold nanoparticles, which were effectively used for enhancement of signal in IR absorption and Raman scattering, metal-enhanced fluorescence, has been studied also. Different roughness of gold surface leads to changes in an enhancement factor. The structural features of bovine serum albumine (BSA) – colloidal gold system and enhancement of guanine that obtained in SEIRA experiment are discussed. Atom force microscopy (AFM) technique was applied to test the roughness of the metal surface. We made an attempt to model the factor of enhancement of electrical field and its frequency dependence for different metal surfaces, and ascertained that silver, gold and copper are the best.